Publicystyka przebrana za literaturę = Journalism disguised as literature - Musiał, Jan (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The author analyses prose works of contemporary - from the beginning of this century - Polish columnists (Andrzej Horubała, Cezary Michalski, Grzegorz Miecugow, Bronisław Wildstein, and Rafał Ziemkiewicz). He wonders whether their works are reflecting the authors' beliefs, inhibi tions, or only their journalistic techniques. The author refers to the example of Ansgar Nunning, who analyses the tasks of literary studies, as confronted with the phenomenon of shaping world views by prose literary genres, and the other way round - the influence that literary "ways of world making" has on non-literary reality.
Keywords: quasi-sądy; upodobnianie gatunków; interdyskurs reintegracyjny; quasi-judgements; genres resemblance; reintegration discourse